Testosterone in yak bull seminal plasma and its correlation with physical characteristics of semen - HAZARIKA, D; SARMA, S; CHAKRAVARTY, P; KALITA, D J; GOSWAMI, J; DEKA, B C (The Indian Journal of Animal Sciences, 2012)
Studies were conducted to estimate testosterone concentration in seminal plasma and its correlation with some seminal characteristics of yak semen. The colour of semen varied from milky white to creamy. The average mean values for ejaculate volume, initial sperm motility, sperm concentration, pH, live sperm and testosterone were 2.83±0.08 ml, 71.5±0.57 %, 1182.5±3.23 million/ ml, 6.34±0.02, 80.05±0.74 % and 1.82±0.08 ng/ml respectively. Significant positive correlation existed between testosterone concentration in seminal plasma with initial sperm motility and live sperm count. The present study revealed that an increase in the levels of testosterone in seminal plasma enhanced certain qualitative parameters (initial sperm motility and live sperm) of yak semen during winter.